AL MULLIM AL MUTAJADDIN F Î TA'L ÎMI AL LUGHAH AL ARABIYYAH LIGHAIRI AL NATHIQINA BIHÂ F Î 'ASRI AL HÂD Î WA AL 'ISYR ÎNA - Ibnu Hafid Alfarisy; Hanik Mahliatussikah (Universitas Negeri Malang, 2019)
المستخلص: المعلم أهم العناصر في التعليم. والمعلم المتجدد في تعليم اللغة العربية لغير الناطقين بها هو المعلم الواعي لما يباشره من عصر العولمة. فهو عمدة و عنصر أساسي في تعليم اللغة العربية. إذا صلح المعلم صلحت جميع العمليات التعليمية. فلا بد أن يتجدد ما له من الكفاءات والقدرات لأن المعلم لا بد أن يفكر في المستقبل بعقلية المستقبل ولا بعقلية الماضي. هذا البحث الوصفي الكيفي يهدف إلى اكتشاف كفاءات المعلم المتجدد وخصائصه في تعليم اللغة العربية لغير الناطقين بها، و معرفة تحدياته اليوم و كيفية إعداده ودوره في التعليم في العصر الألفي. و نتائج هذا البحث: (1) أن للمعلم المتجدد في تعليم اللغة العربية لغير الناطقين بها 4 كفاءات لازمة، وهي الكفاءة التعليمية، والكفاءة الشخصية، والكفاءة الاجتماعية، والكفاءة التعليمية، (2) والخصائص اللازمة للمعلم المتجدد هي الخصائص الجسمانية و القدرات العقلية، والخصائص الشخصية، والأكاديمية والمهنية، والأخلاقية و الإنسانية و النفسية، والتقنية والخصائص الأخرى المرتبطة به، (3) و تحديات المعلم المتجدد اليوم تتعلق بالتحديات الثقافية، و التربية المستدامة، و قيادة التغيير و ثورة المعلومات و تمهين التعليم و إدارة التكنولوجيا، (4) و إعداد المعلم المتجدد بثلاث مراحل وهي التأهيل، والتدريب، والتطوير، (5) و دور المعلم في العصر الألفي هو الموجه و اﻟﻤﺮﺷﺪ واﻟﻤﻴﺴﺮ ﻟﻠﺘﻌﻠﻢ. والتعليم المتمركز على الطالب (ٍStudent-Centered Learning) هو التعليم المطلوب في العصر الحاضر.كلمات المفتاح: معلم متجدد، لغة عربية، كفايات، تحديات، إعداد، دور Abstract:Teacher is the most important element in education. The renewed teacher in the teaching of Arabic to non-native speakers is the conscious teacher of the era of globalization. He is a mayor and a key element in teaching Arabic. If the teacher reconciles all educational processes. It must be renewed its competencies and capabilities because the teacher must think in the future mentality of the future or the mentality of the past. This qualitative descriptive research aims to discover the competencies of the renewed teacher and its characteristics in teaching Arabic to non-native speakers, and to know its challenges today and how to prepare it and its role in education in the millennium. The results of this research: (1) that the renewed teacher in teaching Arabic to non-native speakers 4 necessary competencies, namely, educational competence, personal competence, social competence, and educational competence, Personal, academic, professional, ethical, human, psychological, technical and other characteristics associated with it, (2) The characteristics necessary for the renewed teacher are the physical characteristics, mental abilities, personal, academic, professional, ethical, human, psychological, technical, and other characteristics associated with it. Change, information revolution, education apprenticeship and technology management, (3) The challenges of the renewed teacher today relate to cultural challenges, sustainable education, leadership of change, information revolution, apprenticeship of education and technology management (4) The preparation of the renewed teacher in three stages are rehabilitation, training and development, (5) The millennium teacher is the mentor, guide and facilitator of learning. Student-Centered Learning is required in the present era. Key Words: renewed teacher, arabic language, competencies, challenges, preparation, role Abstrak: Guru adalah elemen terpenting dalam pendidikan. Guru pembaharu dalam pengajaran bahasa Arab untuk penutur asing adalah guru yang sadar akan era globalisasi. Dia adalah elemen kunci dalam mengajar bahasa Arab. Jika guru dapat bekerja dengan baik, maka akan baik pula proses pembelajaran. Kompetensi dan kemampuan guru harus selalu diperbaharui dan ditingkatkan karena guru harus berpikir tentang masa depan dengan pola pikir dan mentalitas masa depan dan bukan dengan pola pikir masa lalu. Penelitian deskriptif kualitatif ini bertujuan untuk menemukan kompetensi guru pembaharu dan karakteristiknya dalam mengajar bahasa Arab untuk penutur asing, dan untuk mengetahui tantangannya dan bagaimana mempersiapkannya serta perannya dalam pendidikan di era milenium. Hasil penelitian ini menunjukkan bahwa: (1) guru pembaharu dalam mengajar bahasa Arab ke penutur asing harus memiliki 4 kompetensi, yaitu kompetensi pedagogis, kompetensi kepribadian, kompetensi sosial, dan kompetensi profesional (2) Karakteristik yang harus dimiliki oleh guru pembaharu adalah karakteristik fisik, kemampuan mental, pribadi, akademik, profesional, etika, kemanusiaan, psikologis, teknis, dan karakteristik lain yang terkait dengannya.(3) tantangan guru pembaharu berkaitan dengan tantangan budaya dan keberlangsungan pendidikan, derasnya perubahan dan arus informasi, kompetensi pengajaran dan manajemen teknologi, (4) persiapan guru pembaharu dalam tiga tahap, yaitu keahlian, pelatihan, pengembangan, (5) peran pengajar di milenium adalah sebagai pembimbing, pengarah dan fasilitator pembelajaran. Pendidikan yang berpusat pada siswa adalah pendidikan yang dibutuhkan di era sekarang. Kata kunci: guru pembaharu, bahasa arab, kompetensi, tantangan, persiapan, peran